ZISWaf Intention Through Islamic Philanthropy Organizations: Does Empathy Matter? The Role of the S-O-R Framework and TPB - Saputra, Yudi (Muslim Business and Economics Review, 2024)
This research aims to examine the variables that affect people’s intention to pay zakat, infaq, shodaqoh, and waqf (ZISWaf) through Islamic philanthropy organizations (IPOs) in Indonesia. This research uses the Stimulus-Organism-Response (S-O-R) framework and the Theory of Planned Behavior (TPB) as the model framework. This research is quantitative with primary data, obtained through online surveys by random sampling method, with 145 respondents participating in further analysis stages using SEM-PLS. From the analysis carried out, Islamic religiosity is found to be the variable that most influences ZISWaf intention. As an indirect effect, perceived credibility is significantly proven to mediate the relationship between transaction convenience and ZISWaf intention. On the other hand, empathy is not found to have a relationship with ZISWaf intention. Several arguments may explain why empathy is not proven to be influential variable in the context of ZISWaf. These findings can be used as an academic foundation for IPOs as ZISWaf fund managers, to develop the credibility issues as a strategic step in increasing intention to pay ZISWaf through IPOs. This study makes several recommendations, including the separation of donation types based on time periods. This research offers a comprehensive model, while still considering the proven theoretical framework. From an academic perspective, this research provides a fresh viewpoint to Islamic philanthropy from an empirical-based approach.